PEMANFAATAN NATA DE COCO TERMODIFIKASI ASAM SITRAT SEBAGAI BAHAN BKU MEMBRAN - Kamulyan, Budi; Mardiana, Diah; Syaifudin, Achmad (Jurnal Ilmu Kimia Universitas Brawijaya, 2015)
In order to discover the alternatif of membrane raw material, modification of nata de coco by esterification has been conducted. In this research, it has been done using citric acid and dibutyltin oxide catalyst. This research aims was to determine the effect of esterification on the chemical structure, thermal properties and hydrophilicity of modified cellulose. Reaction of solid state system using closed reactor supporting by mechanical strirer has been done for 3 hours at 155oC. It was used for reacting 5 g of cellulose and 0.3 g of dibutyltin oxide with adding of citric acid were 5, 15, 25, 35 and 45 g. Product characterization were investigated by FTIR spectrophotometry for predicting the chemical structure and thermal properties using DTA. Where as, hydrophilicity was determined by its swelling index of aquades and ethanol up to 6 hours. The result of FTIR spectrum showed that ester cellulose has been produced, indicating by specific peak of carbonyl group at wave number 1733.89 cm-1. DTA thermogram of ester cellulose showed a glass transition at 7.6oC and endothermic peak at 27.6 and 70.5°C, respectively.   In addition, swelling equilibrium of 3 hours has been obtained with swelling index for aquadest and ethanol were 0.209 and 0.361 time, respectively. Key words:citric acid, esterification, nata de coco